2017
DOI: 10.3892/ol.2017.5558
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant KLK4 gene promoter hypomethylation in pediatric hepatoblastomas

Abstract: Abstract. DNA methylation has a crucial role in cancer biology and has been recognized as an activator of oncogenes and inactivator of tumor suppressor genes, both of which are mechanisms for tumorigenesis. Kallikrein-related peptidase 4 (KLK4), has been suggested to be an oncogene in various types of cancer. The aim of the present study was to assess the DNA methylation patterns of the KLK4 gene in cancerous samples harvested from patients with hepatoblastoma (HB). KLK4 mRNA expression levels were detected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Finally, a study demonstrated that RASSF1A methylation levels increase in parallel with the histological subtype (normal liver < fetal type < embryonal type) [50] . It is possible to measure RASSF1A methylation levels in plasma cell-free DNA from HCC patients [51] , a liquid biopsy which could also be applied in HB studies. Therefore, RASSF1A methylation may be a prognostic factor as well as a therapeutic target for HB.…”
Section: Dna Methylation In Hepatoblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a study demonstrated that RASSF1A methylation levels increase in parallel with the histological subtype (normal liver < fetal type < embryonal type) [50] . It is possible to measure RASSF1A methylation levels in plasma cell-free DNA from HCC patients [51] , a liquid biopsy which could also be applied in HB studies. Therefore, RASSF1A methylation may be a prognostic factor as well as a therapeutic target for HB.…”
Section: Dna Methylation In Hepatoblastomamentioning
confidence: 99%
“…A study reported that increased AFP mRNA expression is associated with hypomethylation of the gene promoter, suggesting that DNA methylation modulates AFP expression in HB [105] . Moreover, kallikrein-related peptidase 4 (KLK4) is found to be upregulated in several types of cancer, including prostate cancer [106] , ovarian cancer [107] , and colorectal adenocarcinoma [108] . KLK4 gene expression is also upregulated in HB in association with aberrant promoter hypomethylation [109] .…”
Section: Dna Methylation In Hepatoblastomamentioning
confidence: 99%
“…The kallikrein-related peptidase 4 (KLK4) gene is considered an oncogene and plays an important role in the formation of many tumors, such as gastric cancer and prostate cancer [63]. Studies have shown that in HB, the methylation level of the gene promoter region is reduced, and the expression of KLK4 mRNA and protein is increased [64]. Gene methylation plays an active role in oncogene expression.…”
Section: Dna Methylation Is An Activator Of Oncogenesmentioning
confidence: 99%
“…It has been observed to be involved in the regulation of cell differentiation and proliferation ( Li et al, 2018 ). The RASSF5 gene is highly methylated in numerous tumors, such as neuroblastoma, oral cancer, and liver cancer, suggesting that it may be a potential tumor suppressor ( Djos et al, 2012 ; Liu et al, 2018 ). Another member, IRF8, was also down-regulated in colorectal and BC tumor tissues, involved in antigen capture and response to interferon ( Gatti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%